An efficiency improvement of flexible flow shop scheduling in automotive part company - Fangrit W.; Yap H.J.; Hamza M.F.; Chang S.-W.; Yap K.S.; Wong S.Y. (IOS Press BV, 2023)
Computer software; Machine shop practice; Tabu search; Automotive parts; Earliest due dates; Efficiency improvement; Flexible flow shop; Heuristic solutions; Hybrid tabu search; Scheduling methods; Simulation software; Scheduling